DYNAMICS OF CHRONIC DISEASES TEENAGERS THE KRASNODAR REGION ACCORDING TO THE ENVIRONMENTAL STATE OF THE ENVIRONMENT - V. A. Shashel; L. A. Podporina; A. M. Shashel; G. V. Naumenko; V. A. Vasilenko (Кубанский научный медицинский вестник, 2017)
In this paper we studied the prevalence of chronic diseases among adolescent children for the period 2006–2012 yy in the Krasnodar region. Discussion of trends in growth or reduce the prevalence of different nosology allows conclusions about the possible causes of these phenomena, to assess the relevance and timeliness of preventive measures.